Memory Guides the Processing of Event Changes for Older and Younger Adults - Wahlheim, Christopher N. (J Exp Psychol Gen, 2018)
Memory for related past experiences can guide current perceptions. However, memory can lead one astray if situational features have changed. Thus, to adaptively use memory to guide perception, one needs to retrieve relevant memories and also to register differences between remembered and current events. Event Memory Retrieval and Comparison Theory proposes that observers associatively activate memories of related previous episodes, and that this guides their ongoing perception. Conflicts between previous and current event features can hurt immediate performance, but if changes are registered and encoded they can lead to highly effective encoding of the prior event, current event, and their relationship. Disruption of these mechanisms could play a role in older adults’ greater susceptibility to event memory interference. Two experiments tested these hypotheses by asking participants to watch movies depicting two fictive days of an actor. Some activities were repeated across days, others were repeated with a changed feature (e.g., waking up to an alarm clock or a phone alarm), and others were performed only on Day 2. One week after watching the Day 2 movie, participants completed a cued recall test. Changes that participants detected but did not remember led to proactive interference in recall, but changes that were successfully detected and remembered led to facilitation. Younger adults detected and remembered more changes than older adults, which partly explained older adults’ differential memory deficit for changed activities. These findings suggest a role for episodic reminding in event perception and a potential source of age differences in event memory.